2014
DOI: 10.1080/14616734.2014.941884
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between attachment style and postpartum depression

Abstract: Although an increasing number of studies show an association between adult attachment style and mood disorders, the relationship between adult attachment style and depression associated with childbirth is largely unknown. This study investigated the association between women's attachment style, postpartum depression (PPD), and other risk factors. During the 32nd week of pregnancy, 84 women were interviewed using the Attachment Style Interview. Participants also completed self-report questionnaires about reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 27 publications
6
34
1
4
Order By: Relevance
“…These findings of the present study are partly in consistent with the findings of the studies conducted by Ikeda et al (2014), Karlin et al (2013), Hedman et al (2013), and Karlin et al (2012). To explain these findings, one can refer to various reasons, one of which is the beneficial effects of group therapy.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings of the present study are partly in consistent with the findings of the studies conducted by Ikeda et al (2014), Karlin et al (2013), Hedman et al (2013), and Karlin et al (2012). To explain these findings, one can refer to various reasons, one of which is the beneficial effects of group therapy.…”
Section: Discussionsupporting
confidence: 82%
“…Few studies have been carried out on the impact of cognitive-behavioral group therapy on guilt feeling in different statistical populations. The findings of these studies (Ikeda, Hayashi & Kamibeppu, 2014;Hedman, Ström, Stünkel, & Mörtberg, 2013;Karlin et al 2012) reported the effectiveness of cognitive-behavioral group therapy on guilt feeling. Unfortunately, there is a paucity of research on the impact of treatment on guilt feeling.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research examining risk factors reflecting personality structure, we found that the insecure attachment style was significantly related to PPD, and those with withdrawn styles were the most prevalent in the PPD group (Ikeda et al, 2014). The latter was a new finding that differed from results reported in studies about mothers in Western culture.…”
Section: Introductioncontrasting
confidence: 52%
“…In Japan, depression is experienced by approximately 21% of mothers in the first month following delivery (Ikeda, Hayashi, & Kamibeppu, 2014). Risk factors for PPD include previous depression, anxiety and depressive symptoms during pregnancy, recent stressful life events, lack of social support, and low self-esteem (Boyce & Hickey, 2005;Milgrom et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dual/disorganized attachment is directly associated to psychopathology (Schimmenti and Bifulco 2008), interpersonal problems in adolescence (Schimmenti and Bifulco 2008), and discomfort in romantic relationships in adulthood (Paetzold et al 2015) but also to maladaptive parenting (Busch et al 2008;Goldberg et al 2003). So far, organized insecure attachment strategies were closely linked to depression per se, its duration and severity (Conradi and de Jonge 2009;McMahon et al 2008), and the occurrence of postpartum depression (Bifulco et al 2004;Ikeda et al 2014). Moreover, an association of insecure adult attachment with lower quality of relationship to the baby (Rholes et al 1995;Wilkinson and Mulcahy 2010) and less adequate parenting behavior (Bifulco et al 2009;Haltigan et al 2014) was reported.…”
Section: Introductionmentioning
confidence: 98%